Cryoballoon ablation for persistent atrial fibrillation – Large single-center experience. Issue 6 (December 2016) - Straube, Florian; Hartl, Stefan; Dorwarth, Uwe; Wankerl, Michael; Bunz, Benedikt; Ebersberger, Ullrich; Hoffmann, Ellen
Abstract: Background: Different catheter ablation (CA) strategies have been established in the treatment of persistent atrial fibrillation (persAF). Pulmonary vein isolation (PVI) only might be an option for the initial ablation procedure. There is a paucity of outcome data on second-generation cryoballoon (CBG2) PVI in persAF. Methods: Patients with symptomatic drug-refractory persAF who underwent initial CA of AF were prospectively enrolled and PVI was performed with CBG2. The primary composite endpoint was freedom from AF, atrial tachycardia, or related symptoms after a 3-month blanking period. The secondary endpoint referred to periprocedural complications. Results: One hundred seventy-three consecutive patients (64 ± 10 years, 29% female) with symptomatic drug-refractory persAF were identified. Acute PVI was achieved in 100% of pulmonary veins with the CB technique. The left atrial procedure time was 112 ± 30 min. Major complications occurred in 1.7% (3 of 173 patients) including two phrenic nerve palsies (1%), which resolved until discharge, and one pericardial effusion (0.6%). Follow-up ≥12 months was completed for 157 of 173 patients (91%). Median follow-up was 14 months. At 12 months, the primary composite endpoint was achieved in 129 of 157 patients (82%). However, 22 of 129 patients at risk (17%) were still on antiarrhythmic drugs. A relapse during the blanking period was identified as the only independent predictor for AF recurrence. Conclusion: PVI using the second-generation cryoballoon is a reasonable treatment option for patients with symptomatic drug-refractory persAF with a favorable rate of freedom from AF and a low complication rate.